Structural optimization scheme for acoustic cloaking structures considering general surfaces. Issue 4 (3rd April 2022) - Kim, Ji Wan; Yoon, Gil Ho
ABSTRACT: The present study presents the application of a structural optimization scheme for a Double Split Hollow Sphere (DSHS) based acoustic cloaking structure for irregular surfaces. For acoustic wave cloaking, many scientific devices utilizing phase differences have been developed. Considering the irregular surfaces of objects to be concealed, acoustic wave reflections become complex with random phase differences and determinations of the involved geometric parameters of cloaking structures become impractical. To determine the geometric parameters of acoustic cloaking devices with DSHS systematically, the present study applies a structural optimization scheme. The present scheme computes and minimizes the differences between the acoustic pressures reflected from irregular surfaces and the reference acoustic pressures without irregular surfaces by optimizing the location and geometric parameters of the DSHS. To show the validity of the present scheme, structural optimization problems are solved for several three-dimensional problems with complex and irregular surfaces.